2009
DOI: 10.1099/vir.0.008987-0
|View full text |Cite
|
Sign up to set email alerts
|

Novel anellovirus discovered from a mortality event of captive California sea lions

Abstract: A viral metagenomic study was performed to investigate potential viral pathogens associated with a mortality event of three captive California sea lions (Zalophus californianus). This study identified a novel California sea lion anellovirus (ZcAV), with 35 % amino acid identity in the ORF1 region to feline anelloviruses. The double-stranded replicative form of ZcAV was detected in lung tissue, suggesting that ZcAV replicates in sea lion lungs. Specific PCR revealed the presence of ZcAV in the lung tissue of al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
74
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(74 citation statements)
references
References 37 publications
0
74
0
Order By: Relevance
“…TTV became the prototype of a large group of viral agents with similar genomic organization but a low sequence homology, isolated both in humans and in animals. In fact, in the following years, similar viruses were isolated in other species of vertebrates, including nonhuman primates (chimpanzees, macaques, tamarin monkeys, and douroucouli), pets (dogs and cats), livestock (pigs, cattle, sheep, camels, and poultry), and wild boars, badgers, pine martens, tupaias, rodents, bats, sea turtles, and sea lions [3,5,[23][24][25][26][27][28][29]35]. The natural infection of pigs was first described by Leary et al in 1999 [5]; the first complete genome of Torque teno sus virus (TTSuV) was described by Okamoto in 2002 [3].…”
Section: Discovery and Characterization Of Ttvmentioning
confidence: 99%
See 1 more Smart Citation
“…TTV became the prototype of a large group of viral agents with similar genomic organization but a low sequence homology, isolated both in humans and in animals. In fact, in the following years, similar viruses were isolated in other species of vertebrates, including nonhuman primates (chimpanzees, macaques, tamarin monkeys, and douroucouli), pets (dogs and cats), livestock (pigs, cattle, sheep, camels, and poultry), and wild boars, badgers, pine martens, tupaias, rodents, bats, sea turtles, and sea lions [3,5,[23][24][25][26][27][28][29]35]. The natural infection of pigs was first described by Leary et al in 1999 [5]; the first complete genome of Torque teno sus virus (TTSuV) was described by Okamoto in 2002 [3].…”
Section: Discovery and Characterization Of Ttvmentioning
confidence: 99%
“…Furthermore, a series of closely related TTV-like viruses, and two distinct genera comprising viruses with smaller genome size and similar genetic organization, but only partial sequence homology, designated Torque teno midi virus (TTMDV) and Torque teno mini virus (TTMV), have been characterized [20][21][22]. A large number of AV species has also been reported in wild and domestic animals, including non-human primates, wild boars, badgers, pine martens, tupaias, rodents, bats, sea turtles, sea lions, livestock (pigs, sheep, cattle, camels, and poultry), and companion animals (cats and dogs) [3,5,[23][24][25][26][27][28][29]. Indeed, since to date the presence of TTVs infecting mammalian species has been poorly investigated, it would not be surprising if all mammals were infected with species-specific TTVs.…”
Section: Introductionmentioning
confidence: 99%
“…This is because viruses lack a common phylogenetic marker, and therefore marker-based amplicon sequencing (for example, 16S or 18S ribosomal RNA surveys) cannot necessarily be applied to diverse viral consortia. Some examples of the successful application of viral metagenomics to elucidate the pathogens associated with a disease include the identification of: an astrovirus as the probable cause for shaking mink syndrome (Blomströ m et al, 2010), an anellovirus associated with a California sea lion mortality event (Ng et al, 2009) and a coronavirus that causes human respiratory disease (Bermingham et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…TTV was first detected in a human patient with post-transfusion hepatitis of unknown aetiology [19], but later detected in many other vertebrate animals including pigs [3,7,10,16,21,22]. In pigs, two distinct species of TTV, Torque teno sus virus (TTSuV), types 1 (TTSuV1) and 2 (TTSuV2) have been described [17,22], and they are currently grouped under the genus Iotatorquevirus of family Anelloviridae [2].…”
mentioning
confidence: 99%
“…TTSuV1 and TTSuV2 (TTSuVs) have been detected from serum, plasma, semen, faeces, colostrum, nasal secretion and various tissues [5,8,13,26,29,30] exclusively by Polymerase chain reaction (PCR), and different pig rearing countries have reported prevalence rate ranging from 24 to 100% [4,8,[14][15][16][17][24][25][26]. Limited longitudinal studies employing serum [17,26] and cross-sectional studies employing serum and tissues [1,8,9,27] have shown that TTSuV infection increases with age.…”
mentioning
confidence: 99%